HARNESSING DUAL CODING AND COGNITIVE LOAD THEORY FOR TRANSFORMATIVE EDUCATION IN EASTERN ART HISTORY - Sunjoto, Dwinita Tiaraningrum; Trisakti; Sekti, Retnayu Prasetyanti (EDUCATIONE, 2025)
The use of visual materials is an uncommon practice in art history teaching, including in Eastern Art History courses. Visual materials are believed to help students understand complex cultural and strengthen understanding of abstract concept. This study aims to analyze the cognitive visual learning theory that underlies the teaching practice of the course, especially in terms of the use of visual aids and lecture methods, and to examine its compatibility with visual and cognitive learning theories. This research used a participatory approach with descriptive qualitative methods. Data were collected through classroom observation, semi-structured interviews with students, and analysis of learning documents. Analysis was conducted using thematic matrix technique to identify patterns and themes from the data obtained. The results showed that visual and cognitive learning theories were used in learning. Visual aids such as pictures, slides, and videos help students understand the material more deeply and strengthen memory. Meanwhile, lectures provide a cognitive structure that supports information processing. Students stated that the combination of visual and verbal is very important in improving their understanding of Eastern Art History materials. This reseach confirm the importance of aligning practice and learning theory.